2020
DOI: 10.3390/transplantology1020011
|View full text |Cite
|
Sign up to set email alerts
|

The Revolution in Indication for Liver Transplantation: Will Liver Metastatic Disease Overcome the End-Stage Liver Disease in the Next Future?

Abstract: Indications for liver transplantation (LT) have constantly been evolving during the last few decades due to a better understanding of liver diseases and innovative therapies. Likewise, also the underlying causes of liver disease have changed. In the setting of transplant oncology, recent developments have pushed the boundaries of oncological indications for LT outside hepatocellular carcinoma (HCC), especially for secondary liver tumors, such as neuroendocrine and colorectal cancer. In the next years, as more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Notably, the reports in our study focused only on FAP; therefore, it was not possible to explore the impact of DLT on waiting list times when considering other indications, such as other metabolic disorders. At present, while there is a constant shortage of transplantable organs, the number of indications for LT is expanding, especially for secondary liver tumors and metastases 21 . In the future, DLT could be a compelling option to expand donor pool and enable transplantation of patients even with biologically unfavorable liver tumors or metastatic diseases, who might have limited access to organs, especially in countries with longer waitlist times and where the number of deceased donors is limited 22–24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the reports in our study focused only on FAP; therefore, it was not possible to explore the impact of DLT on waiting list times when considering other indications, such as other metabolic disorders. At present, while there is a constant shortage of transplantable organs, the number of indications for LT is expanding, especially for secondary liver tumors and metastases 21 . In the future, DLT could be a compelling option to expand donor pool and enable transplantation of patients even with biologically unfavorable liver tumors or metastatic diseases, who might have limited access to organs, especially in countries with longer waitlist times and where the number of deceased donors is limited 22–24 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, while there is a constant shortage of transplantable organs, the number of indications for LT is expanding, especially for secondary liver tumors and metastases. 21 In the future, DLT could be a compelling option to expand donor pool and enable transplantation of patients even with biologically unfavorable liver tumors or metastatic diseases, who might have limited access to organs, especially in countries with longer waitlist times and where the number of deceased donors is limited. [22][23][24] In our study, we were able to demonstrate similar long-term recipient survival rates between DLT and DDLT.…”
Section: Domino or Deceased Livers: Meta-analysismentioning
confidence: 99%
“…On top of this, the recent advances in transplant oncology showed that LT can be an effective treatment for other types of primary and secondary liver cancers beyond hepatocellular carcinoma. These types of evidence could change the trends in indication for LT [2].…”
mentioning
confidence: 99%